EFEKTIVITAS STRATEGI PENYESUAIAN MAHASISWA BARU PADA PROSES PEMBELAJARAN DI PERGURUAN TINGGI. (STUDI PADA UPN ”VETERAN” JAWA TIMUR) - Mei Retno Adiwaty; Zumrotul Fitriyah (Trunojoyo University of Madura, 2015)
The more competitive of education world, will make an university to have competitive adventage. In order to survive an university should be able to provide facilities that can support learning process. So that student can adjust to the environment.The aims of this study was to analyse the effectiveness of adjustment strategies for new student in the learning process. This study used primory data, collected from questionare, whith is distributed to 146 students UPN “Veteran” Jawa Timur. Technique analysis used PLS (parsial Least Square) which used to test the hypothesis : the more appropriate adjustment strategy, will make the better students learning process in higher education.The causality test showed that copying strategies has positive effect on adjustment process (accepted). This result showed indicator of emotional focus copying has the biggest loading factor. It means that students more dominant focused on emotional focus copying to solve their self adjustment